Experimental Investigation on Hydroabrasive Erosion of Steel Fiber UHPC and Rubber UHPC - Shuangxi Li; Liang Tang; Wenyou Shi; Congchun Zhong (Advances in Materials Science and Engineering)
Steel fiber ultrahigh performance concrete (UHPC) and rubber ultrahigh performance concrete (UHPC) adopt the methods of “rigidity overcomes rigidity” and “softness overcomes rigidity,” respectively, to resist the abrasion and cavitation erosion caused by water flow carrying large solid particles. The above two have been applied in engineering successfully, but there are differences in material properties, mechanical properties, and microstructures. In this study, we will analyze the difference of abrasion resistance performance of the above two kinds of UHPC, in terms of, for example, compressive strength, abrasion resistance strength, abrasion rate, and microstructure in different ages, so as to provide a new material and method. The results indicate that the steel fiber UHPC compressive strength is higher than that of rubber UHPC (containing 1% steel fiber), and the abrasion resistance performance of steel fiber UHPC is lower than that of rubber UHPC (containing 1% steel fiber) when the rubber content is 10% and 12.5%. With the increase of steel fiber content, the compressive strength of steel fiber UHPC is not significantly improved, and the influence of water-binder ratio (W/B) on UHPC is higher than that of steel fiber content. With the increase of rubber content, the rubber UHPC compressive strength decreases, abrasion resistance strength decreases, and abrasion rate increases. The cement paste-aggregate interface transition zone (ITZ) of steel fiber UHPC and rubber UHPC has few internal voids and high compactness; however, the ITZ of steel fiber UHPC is denser than that of rubber UHPC.